2021
DOI: 10.1108/bfj-08-2021-0941
|View full text |Cite
|
Sign up to set email alerts
|

Quality perception throughout the table egg supply chain

Abstract: Purpose:This research shows how the perception of quality differs through the table egg chain and highlights the main quality characteristics for each studied chain participant (farm, retail, consumer).Design/methodology/approach:Observing the change in perception starts from the farm, through retail to the end consumer using the customer–supplier interaction, while looking back from the consumer to the farm, the application of the quality function deployment (QFD) was used. The study included 30 farms, 50 ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 56 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…The analysis included farm–retail and retail–household interactions. The Mann–Whitney (U) test was used to determine ranking differences at a statistical significance level of 0.05, as in the work of Mitrovic et al [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…The analysis included farm–retail and retail–household interactions. The Mann–Whitney (U) test was used to determine ranking differences at a statistical significance level of 0.05, as in the work of Mitrovic et al [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, their results also showed that packaging and brand name are the least important for consumers. Results of a recent study also showed price and size to be the determining factors for consumers in egg purchases (Berkhoff et al, 2020), whilst according to Mitrovic et al (2022) consumers appreciate most shelf life, type of production, egg size and shell appearance.…”
Section: Conceptual Frameworkmentioning
confidence: 97%
“…Doyon et al, 2016). Furthermore, production system has been considered as one of the most significant factors influencing consumers' purchase decisions for egg products in the UK (Parrott et al, 2016) and in Serbia (Mitrovic et al, 2022). Also, evidence also exists on consumers' willingness to pay higher prices for adding objects in barn systems, such as perches and nesting boxes (Doyon et al, 2016) and removing the beak trimming practice from production (Ochs et al, 2018).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Eggs are considered a perishable food product where careful preservation and storage is extremely important to guarantee the nutritional value and freshness (Braun, 2000; Gałązka‐Czarnecka et al ., 2019). Unambiguously, the journey from farm to table presents with different challenges, with a significant percentage of eggs rendered uncollectable due to issues ranging from cracked shells to transportation and storage‐related factors, including those affecting freshness (Mitrovic et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%